Electrodeposition Mechanism of Cathodically-Prepared Manganese dioxide Thin Films from Permanganate for use in Electrochemical Capacitors. (10th May 2017) - Gibson, Andrew J.; Latham, Kenneth G.; Burns, Robert C.; Donne, Scott W.
Abstract: Herein the various steps in the electrodeposition mechanism of manganese dioxide from permanganate are elucidated. Two primary mechanisms are described, dependent on applied potential and hydrodynamics. The first is a combined reduction and disproportionation reaction involving the reduction of MnO4 − to MnO4 2−, which subsequently hydrolyses and disproportionates to form the Mn(V) species H2 MnO4 − . This is then further reduced to form manganese dioxide. This reaction continues over the whole potential range, however whether the system is dynamic or static has an effect on this, with the former leading to continued reaction from an influx of MnO4 −, and the latter not having available MnO4 − to proceed. The second mechanism involves a dissolution of already existing manganese dioxide, through a MnOOH intermediate to form aqueous Mn 2+ . This Mn 2+ then reacts with MnO4 − in solution to form manganese dioxide. These mechanisms have been substantiated with scanning electron microscopy and X-ray photoelectron spectroscopy. The performance of these materials as capacitor electrodes has also been investigated, achieving 363 F/g when cycled at 25 mV/s.